PARTISIPASI IBU RUMAH TANGGA DALAM KEGIATAN MAJELIS TAKLIM DI RT 02 RW 04 KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Sari, Laila Fitria Sari Fitria; Bahar, Aswandi Bahar; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is motivated high participation of housewives in the activities of the Assembly Taklim in RT 02 RW 04 kelurahan Tuah Karya Kecamatan Tampan Kota Pekanbaru. The research problems are how high the participation of housewives in the activities of the Assembly Taklim in RT 02 RW 04 Kelurahan Tuah Karya Kecamatan Tampan Kota Pekanbaru. The purpose of this study was to determine the participation of housewives in Taklim Assembly activities in RT 02 RW 04 Kelurahan Tuah Karya Kecamatan Tampan kota Pekanbaru. The population in this study as many as 50 people housewives and the sample 20 housewives, the sample used is simple random sampling (random sampling). Instrument collecting data questionnaire with 65 statements and after the trial lived 62 valid statement to be made in the instrument of research. Data analysis through quantitative descriptive analysis. Participation housewife against Taklim Assembly activities in RT 02 RW 04 Tuah village sub-district work Handsome is high, with the average percentage (SS + S) 77.63%. Keywords: Participation, Participation housewife, Activity Majelis Taklim